The effect of the independent learning strategy on the achievement of fifth graders in Science - Hanan Kazem Abd ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The researcher has prepared a multiple-choice test. It is a post-test consisting of twenty items in which respondents are asked to select only correct answers from the choices offered as a list. The test items cover Unit Four (Power and Energy) and Unit Five ( Earth and its Sources) in the textbook of Science of 5th primary grade. The test has been subjected to a jury of experts in measurement and evaluation and methods of teaching science. 80% of the jury have agreed to maintain all the items of the test with some amendments. The final version of the test has been administered to sixty-pupil pilot sample chosen from Al-Asood School for Boys to determine the psychometric characteristics of the test. SPSS has been used for statistical analysis (see the results in Appendix 4). Finally, the test has been administered to fifty-pupil sample on 3rd May 2019 . This sample comprises the experimental group and the control group. The results have revealed statistically significant difference between the mean scores of the experimental group and the control group at 0.05 significance level. The t-test (see Table 5) has revealed that the achievement of the experimental who were taught by independent learning is higher than that of the control group who were taught by the conventional method. DOI /10.54633/2333-021-042-024